Specificity of Ransomware Investigation: Analytical Study in Light of the European Cybercrime Programmed 2022 - BOUFLIH, Mohamed Said; CHAIBI, Abdeldjabar (Journal of Human Sciences, 2025)
This research article deals with the topic of ransomware attacks that have recorded a significant increase during the COVID-19 pandemic due to the large technology and digital services companies allowing their employees to work from home using their personal computers and enabling them to use passwords to access internal networks to complete the tasks assigned to them, where the negligence of some employees enabled hackers and intruders to use malicious software to penetrate networks and access companies' data and successfully encrypt them and then demand a ransom later.This study allows for a close look at the most important details of launching ransomware attacks, and the methods used to collect criminal money, then addressing the European Union's guidelines for law enforcement agencies (judges, investigators) in investigating and investigating ransomware attacks to identify the attackers and ensure their prosecution, by presenting a guide in late 2022.